Lung metastasis of adenoid cystic carcinoma, which mimicked primary lung cancer. Issue 3 (24th July 2013) - Ito, Masaoki; Okita, Riki; Tsutani, Yasuhiro; Mimura, Takeshi; Kawasaki, Yukari; Miyata, Yoshihiro; Okada, Morihito
Abstract: We report a case of adenoid cystic carcinoma of the submandibular gland where pulmonary metastasis occurred twice 16 years after resection, and each metastasis mimicked primary lung adenocarcinoma in imaging findings. The first pulmonary relapse was clinically diagnosed as primary lung adenocarcinoma and intraoperative pathological examination showed that the tumor was an adenocarcinoma; lobectomy with mediastinal lymph node dissection was performed. However, postoperative immunohistochemical analysis showed that the tumor was a metastatic adenoid cystic carcinoma. During the secondary pulmonary relapse, although the tumor was correctly diagnosed as a metastatic adenoid cystic carcinoma by intraoperative examination, it again mimicked primary lung adenocarcinoma.